PRESS AND POLICY IN PARANÁ: A PROSOPOGRAPHY OF THE REPUBLICAN REDEEMERS. - Amélia Siegel Corrêa (Clio: Revista de Pesquisa Histórica, 2006)
The crisis of the Brazilian monarchist regime was accompanied by the emergence and expansion of the republican movement in the late nineteenth century. In the period, the press not only became the stage of institutional debates, but also played an in-formal role. In order to better understand the networks and configurations that led to the production and diffusion of Republican ideas in Paraná, a prosopography was elaborated by the writers who discussed the republican question in the local press. The collective biography also allowed the understanding of the various political positions in the networks that influenced the local republicanism, which, in its dominant strand, was linked to the project of conservative modernization of the iberian elites, who had economic and political capital that allowed state control after the Proclamation of the Republic. As the intellectual field had not yet been configured, the writers analyzed were linked to the political field.